Microsatellite analysis of populations of the endangered tree Gomortega keule suggests pre-Columbian differentiation - Munoz-Concha, Diego; Davey, Michael R.; Ribas, Gracia; Mayes, Sean (Taylor & Francis, 2017)
Temperate forests have been affected extensively by human activities, resulting in land cover changes and population fragmentation. However, these anthropogenic effects can be superimposed onto the natural history of species, making it difficult to determine which effect is more important for a particular species. Gomortega keule is an endangered tree that is found in one of the world’s biodiversity hotspots in central–south Chile. Human activities have significantly impacted on the original habitat in this region in recent years and are commonly considered to be the main cause of the scarcity of this species. However, aspects of the natural history of this evergreen tree may also help to explain its present-day genetic structure. In this study, we undertook microsatellite genotyping of the two southernmost populations of G. keule, which are 7.5 km apart and well isolated from other populations. We found that there was genetic differentiation between these populations, suggesting that they exhibited at least some differentiation before becoming isolated, most likely before human activities first impacted the region some two centuries ago. Molecular estimates of their divergence time supported a more ancient differentiation of the populations than would be explained by human activities alone. It is possible that their isolation may have followed the extinction of megafaunal seed dispersers around 12,000 years before present in this region, as indicated by fruit characteristics, the absence of recruitment by seedlings and the existence of clonal trees.